A Narrative Inquiry of Two English Teachers' Identity Construction - Devia Fitaloka; Isti Siti Saleha Gandana (Siliwangi University, 2023)
Teacher identity is one of the essential aspects influencing the form and quality of educational processes. The present study examines the narratives of one of the writers, Devia, and an English teacher, Trisa, throughout their learning and teaching experiences and the process that were involved as they negotiated their identities as teachers. The data were collected from an autobiographical narrative of Devia as an English teacher, as well as intensive life-history interviews with Trisa. Analysis of the narratives and interview data led to four major themes: inspiring figures, teaching practicum experiences, becoming an English teacher, and pursuing a postgraduate study. The findings revealed that Deviaâ€™s and Trisaâ€™s engagement in the practices and activities of learning and teaching shaped their teacher identity constructions.Â Keywords: narrative inquiry, teacher identity, teacher identity construction